1996
DOI: 10.1126/science.272.5269.1804
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant B Cell Development and Immune Response in Mice with a Compromised BCR Complex

Abstract: The immunoglobulin alpha (Ig-alpha)-Ig-beta heterodimer is the signaling component of the antigen receptor complex on B cells (BCR) and B cell progenitors (pre-BCR). A mouse mutant that lacks most of the Ig-alpha cytoplasmic tail exhibits only a small impairment in early B cell development but a severe block in the generation of the peripheral B cell pool, revealing a checkpoint in B cell maturation that ensures the expression of a functional BCR on mature B cells. B cells that do develop demonstrate a differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
206
3

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 272 publications
(220 citation statements)
references
References 56 publications
(11 reference statements)
11
206
3
Order By: Relevance
“…Several in vivo studies have shown that expression and signaling of the pre-BCR and BCR are prerequisite to complete the development of B lymphocytes (15,16,18,19,32,33,(57)(58)(59)(60). We find that Ig-␣-deficient mice have a block in B cell development that is similar to mice lacking Ig-␤ or m expression.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Several in vivo studies have shown that expression and signaling of the pre-BCR and BCR are prerequisite to complete the development of B lymphocytes (15,16,18,19,32,33,(57)(58)(59)(60). We find that Ig-␣-deficient mice have a block in B cell development that is similar to mice lacking Ig-␤ or m expression.…”
Section: Discussionsupporting
confidence: 52%
“…Mice bearing mutations in or deletions of the cytoplasmic portion of both Ig-␣ and Ig-␤ also show complete block at the pro-B cell stage of B cell development (17,18). However, the same mutations in either Ig-␣ or Ig-␤ cause a partial block at the pre-B cell stage and a more severe arrest at the immature B cell stage, demonstrating that Ig-␣ and Ig-␤ have redundant signaling functions, at least during pre-BCR signaling (17)(18)(19).…”
Section: B Cell Progenitors Are Arrested In Maturation But Have Intacmentioning
confidence: 99%
“…Finally, knockout models of the last two components of the pre-BCR complex, CD79a and CD79b, 14,15 provide evidence for their requirement in B-cell differentiation in the bone marrow, in particular in the V-DJ rearrangement process. Recently, two patients were found to have homozygous defects in Iga: 16,17 comparison with mHCdeficient patients reveals, in both cases, a block at the early stages of B-cell development and similarly impaired V-DJ rearrangements.…”
Section: Introductionmentioning
confidence: 98%
“…The cytoplasmic tails of Igα and Igβ each contain an immunoreceptor tyrosine‐based activation motif (ITAM) with two conserved tyrosines that are crucial for the development and maintenance of mature B cells (Reth, 1989; Torres et al , 1996; Kraus et al , 2001, 2004; Reichlin et al , 2001). Upon antigen ligation and opening of the BCR, the spleen tyrosine kinase (Syk) phosphorylates and interacts with the ITAM tyrosines of Igα and Igβ (Rolli et al , 2002).…”
Section: Introductionmentioning
confidence: 99%